Optimization of multi-digit Multiplication based on FFT in Parallel computational model - Терещенко, Андрій Миколайович (Ukrainian Information Security Research Journal, 2015)
It is considered the operation of multi-digit multiplicationfor parallel computational model, that has biggest influenceon performance of asymmetric cryptographic computer systems. It is given modification of N-digit multiplicationalgorithm based on FFT and DTF`s coefficientspreviously computed. New algorithm operates with multidigitsof the length of N, contrary to standard algorithmthat uses multi-digits of the length of 2N. Algorithm reducesin two times the number of used parallel processorskeeping the same computational complexity of each processorin comparison with standard algorithm. Givenalgorithm is also efficient in sequential computationalmodel.